(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The aim of the research was to substantiate the amount of propellant in the composition of the aerosol concentrate, depending on the consumption characteristics of the film formed on the wound surface. The publication experimentally substantiates the concentration of propellant chladon-134a, which is a necessary component for the formation of a film-forming aerosol. Materials and Methods: The authors used modern research methods: Pharmacotechnological and physicochemical – to substantiate the optimal amount of propellant in the composition of the developed aerosol film forming. Results: Studies have shown that the type and amount of propellant affects the film formation. The authors found that depending on the amount of propellant in the balloon, the type of delivery of the solution from the balloon will change – or sprayed, or removed smoothly; the appearance of the film depends on the amount of propellant – smooth, shiny, as well as the percentage of concentrate dispensing from the aerosol container. Discussion and Conclusion: Physicochemical studies have proved the influence of propellant on the technological parameters of the film-forming aerosol: Type of delivery, appearance – colorless film with a smooth shiny surface; film thickness – 10–200 μ; drying time – 10–15 min; and the percentage yield of the contents of the aerosol container – 97.84 ± 2.31%. The use of propellant chladon 134a at a concentration of 10% was found to be optimal. At this concentration, the highest percentage yield of the contents of the aerosol container is ensured, which allows to obtain a film with a smooth type of delivery and satisfactory consumer characteristics.